Biomarkers and subclinical atherosclerosis - Panayiotou, Andrie (My University, 2008)
In this thesis, the relationship between biomarkers and subclinical atherosclerosis as assessed by ultrasonic measurements, other than the commonly used intima-media thickness, such as presence of plaques and number of bifurcations with plaque, plaque size and echodensity has been studied. A cohort of 767 volunteers underwent duplex scans of both carotid and femoral artery bifurcations. A detailed medical history was taken and a clinical examination was made. 50 biomarkers (both biochemical and genetic) were chosen. They involved markers of lipid metabolism, endothelial dysfunction, inflammation, thrombosis, homocysteine metabolism and insulin resistance. A number of biomarkers have been shown to be associated with the ultrasonic measurements studied. These were the apoB/apoA1 ratio, Lp-PLA2 activity, the apoE (E2/E3/E4), CETP (TaqIB1B2 and I405V), MGP (-138C>T) and MMP-9 (R279Q) genetic polymorphisms, sCD40L, fibrinogen, tissue factor, tHcy, vitamin B12, MetS components and insulin sensitivity (HOMA). In addition, an association between Lp-PLA2 activity levels and the Lp-PLA2 A379V polymorphism, in women only, was shown. Results indicate that if precise phenotypes for subclinical atherosclerosis are used a combination of genetic, biochemical markers (tested here) and conventional risk factors can explain up to 37% of the variability in ultrasonic measurements of the arterial wall. The contribution of the biomarkers tested here was of the order of 7%. An important finding of the study is the confirmation by our data of recent hypotheses that different markers are associated with different stages of atherosclerosis. Furthermore, this is the first report of an association between Lp-PLA2 activity levels and Lp-PlA2 A379V genotype in a general population setting; also between Lp-PLA2 activity and subclinical atherosclerosis. In the presence of an association between Lp-PlA2 activity and CHD as shown by two other studies, our finding of an association between Lp-PLA2 activity and A379V genotype in women suggests evidence of causality.
Keywords: Atherosclerosis; Atherosclerosis research; Genetic biomarkers; Genetic polymorphisms; Atherosclerotic plaque; Ultrasonics in medicine